Supplementation of stocker steers grazing native Flint Hills pasture with a protein and mineral supplement increases average daily gains - B.B. Barnhardt; M.P. Epp; A.M. Bryant; P.J. Guiroy; Dale A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2007)
Supplementation of range cattle with minerals is a common management practice that is used to maximize performance. Flint Hills grasses provide an adequate amount of protein for the diet through the first half of a doublestock grazing period, but declining protein content of native grasses during the latter parts of the grazing season typically cause decreases in forage digestibility and daily gains. The goal of this experiment was to measure differences in performance between steers that were supplemented with a) loose salt for the entire grazing period, b) a stocker mineral supplement for the entire grazing period, or c) a stocker mineral supplement for the first half of the grazing period followed by supplementation with a combination of protein and mineral for the second half of the grazing season.
Keywords: Cattlemen' s Day; 2007; Kansas Agricultural Experiment Station contribution; no. 07-179-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 978; Beef; Cattle; Stocker steers; Avergage daily gain (ADG)